2020
DOI: 10.1111/grow.12431
|View full text |Cite
|
Sign up to set email alerts
|

Does household laborer migration promote farmland abandonment in China?

Abstract: This paper investigates the effects of household labor migration on rural household decision making over on the abandonment of farmland using 11,413 rural households' data from 2012 to 2016 in China. The results demonstrate that with every 1% increase in the number of 1, 2, 3, or more household migrant laborers, the average probability of rural households' farmland abandonment increases by 2.9%, 5.0%, and 7.8%, respectively. There is an inverted U‐shaped relationship between the average age of household migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Research has shown that migration is associated with land abandonment in other contexts, for example, in rural China where labour migration has been identified as an important determinant of farmland abandonment [2,8,9,48]. This suggests that land abandonment information could be used in studies of e.g.…”
Section: Using Land Abandonment To Study Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that migration is associated with land abandonment in other contexts, for example, in rural China where labour migration has been identified as an important determinant of farmland abandonment [2,8,9,48]. This suggests that land abandonment information could be used in studies of e.g.…”
Section: Using Land Abandonment To Study Migrationmentioning
confidence: 99%
“…Land abandonment describes the discontinuing of agricultural activities, which often leads to subsequent recovery of natural vegetation [3]. The causes behind land abandonment are complex and include biophysical as well as political and socioeconomic drivers, such as unsuitable climate conditions, drought, small field sizes, government policies, and migration [2,3,[5][6][7][8][9]. Migration caused by armed conflict may also lead to land abandonment [10,11], but in some cases cultivation may continue as the land becomes occupied by new groups [12].…”
Section: Introductionmentioning
confidence: 99%
“…Urban expansion encroaches on extensive farmland areas and negatively impacts agricultural landscape patterns, a decline in agricultural land-use intensity (Jiang et al, 2013;Su et al, 2014;Yu et al, 2019). Combining with remittance effects, rural-urban migration promotes their cropland abandonment (C. Lu, 2020;Lorenzen et al, 2020). The conversion of agricultural land to urban uses leads to rapid transformations in rural areas' agricultural production (Thuo, 2013).…”
Section: Expansion Of Land Usagementioning
confidence: 99%
“…Rapid urbanization and industrialization have led to significant rural degradation in China, which manifests in a large reduction of the rural population, aggravation of aging population, marginalization of land, abandonment of housing, and low‐quality infrastructure (Bai et al., 2014; Li et al, 2014; Liu et al., 2013; Long et al., 2012; Lu, 2020). Meanwhile, a large proportion of rural construction land remains idle, further constraining rural development.…”
Section: Background On Rcr In Sichuan Province Chinamentioning
confidence: 99%